Pengaruh Natrium Sulfat Terhadap Kekuatan Impact Dan Kerusakan Batu Tempel Plastik-Pasir Dan Batu Apung - Lasrio, Jonathan; Suardana, Ngakan Putu Gede; Kencanawati, Cok Istri Putri Kusuma (Teknik Desain Mekanika; Vol 10 No 4 (2022): Oktober 2022 : Teknik Desain Mekanika, 2022)
Abstract Garbage0is somethingothat is no longer used and is discarded from the activities of living things. In Indonesia, waste production reached 34,511,278.65 tons in 2020, 17.1% of which was plastic waste. The substances contained in plastic waste are very dangerous for human health and can also cause environmental pollution. This research was conducted based on one of the 3R principles, namely recycle. HDPE type of plastic waste is processed into outboard stone where plastic is used as a fisher with sand and pumice (1:2:1). The tests carried out were damage test by immersion with 5%, 10%, and 15% sodium sulfate for 30 days, impact test and micro photo test. As a comparison, the same test was also carried out on Silakarang sandstone. The immersion of 15% sodium sulfate caused the highest damage to the specimen, which was 1.72% on the plastic paste stone. The data from the highest impact test was plastic outboard stone without sodium immersion, which was 0.0073 J/mm2. The results of the micro photo test can see the surface morphology of the composite. The test results showed that the composite paste stone without immersion had the highest value. Treatment with higher concentrations of sodium sulfate resulted in higher damage and lower impact strength. Key Word : Paste stone, Sodium sulfate, Impact test, High Density Polyethylene